Theoretical Implications of a Pre-Erythrocytic Plasmodium vivax Vaccine for Preventing Relapses. Issue 4 (April 2017) - White, Michael; Amino, Rogerio; Mueller, Ivo
Abstract : Preventing malaria infection through vaccination requires preventing every sporozoite inoculated by mosquito bite: a major challenge for Plasmodium falciparum . Plasmodium vivax sporozoites consist of tachysporozoites causing primary infection and bradysporozoites leading to relapses. We hypothesise that a candidate P. vivax vaccine with low efficacy against primary infection may substantially reduce transmission by preventing relapses.